DESERT AND SEMI-DESERT VEGETATİON OF GARAGUSH MOUNTAIN - Novruzi , N. (EurasianUnionScientists, 2021)
Desert and semi-desert vegetation It is observed in the form of a narrow strip from north to south, and local spots in the direction of Ordubad region after the Araz Lake. It covers the areas of 600-1000 meters in the plains of Sadarak, Sharur, Boyukduz, Nakhchivan, Gulustan, Yayji, Desta and Ordubad. Some of the typical desert elements have been found in the foothills of Mountain Garagush, especially in the Gendara zone. Of these species, Amaranthaceae Juss. , (Chenopodiaceae Vent.) Suaeda dendroides Mog, belonging to the genus Chenopodiaceae. - Woody herb, Halocnemum strobilaceum (Pall.) Bieb. - Condensed sorrel and Seidlitzia florida (Bieb.) Bunge are examples of flowering marigold species. However, it is possible to claim that the desert vegetation was not fully formed, but that the desert vegetation formed a transition to semi-desert vegetation. Demiler, Gendera, Sariagil, Ramlar and Lizbird valleys of Garagush Mountain have local salinity, ephemeral-gallant (colored soil), gamma (gypsum soil) and sandy areas. The latter sandy area is more noticeable in the Lisbird Valley.